A Novel Biasing Scheme of Electrolyte‐Gated Organic Transistors for Safe In Vivo Amplification of Electrophysiological Signals. Issue 11 (3rd March 2022) - Di Lauro, Michele; Zucchini, Elena; De Salvo, Anna; Delfino, Emanuela; Bianchi, Michele; Murgia, Mauro; Carli, Stefano; Biscarini, Fabio; Fadiga, Luciano
Abstract: Successful translation of organic transistors as sensors and transducers to clinical settings is hampered by safety and stability issues. The operation of such devices demands driving voltages across the biotic/abiotic interface, which may result in undesired electrochemical reactions that may harm both the patient and the device. In this study, a novel operational mode is presented for electrolyte‐gated organic transistors that avoid these drawbacks: the common‐drain/grounded‐source configuration. This approach reverts the standard common‐source/common‐ground configuration and achieves maximum signal amplification while applying null net bias across the electrolyte, with no parasitic currents. The viability of the proposed configuration is demonstrated by recording in vivo the somatosensory evoked activity from the barrel cortex of rats. The main inherent advantage of transistors with respect to passive electrodes is preserved in the proposed scheme: a superior signal‐to‐noise ratio is achieved which enables the detection of evoked activity at the single‐trial level. Then, common‐drain/grounded‐source organic transistors are proposed as ideal candidate devices for a harmless translational recording platform. Abstract : The common‐drain/grounded‐source electrolyte‐gated organic transistor is presented and validated in vivo for brain interfacing. This novel operational mode ensures electrochemical safety in organic first‐stage amplifiers for electrocorticography, achieving superior signal‐to‐noise ratio and single‐trial event recognition, paving the way toward translational organic bioelectronics.